(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Gastric resection syndrome is a complex of various symptoms that occur in patients after surgical removal of a part of the stomach. The main reason for the development of this syndrome is a violation of the normal digestive process, which can lead to various unpleasant sensations and complications. Patients who have undergone resection often experience symptoms such as diarrhea, abdominal pain, feeling full, and nausea. These symptoms are caused by changes in the anatomy and physiology of the digestive system. A decrease in stomach volume affects the rate of digestion and absorption of nutrients, which can lead to vitamin and mineral deficiencies.